PROBLEMS AND DIRECTIONS FOR IMPROVEMENT OF CALCULATION ACCOUNTS AT THE TAX ON ADDED COSTS ON ENTERPRISES OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The value added tax is the main fiscal tool for filling the State budget of Ukraine. The correctness of primary accounting and reflection in the accounts of such components as the VAT tax liability and tax credit depends on completeness and timeliness of calculations of the enterprise with the budget for this tax. In accordance with this relevance determination problem of accounting for the settlement of businesses for VAT and identify possible directions of its improvement in the context of recent changes and additions to the current legislation.On the basis of generalization of the approaches of leading scientists and to the requirements of the Tax code of Ukraine in the article the author’s approach to definition of the essence of the value-added tax on the basis of which VAT is an indirect state tax, which is a component of the price of goods, works and services, including tax obligations and the tax credit for the supply of goods (works/services) as well as obligations of a business entity (legal entity or natural person-entrepreneur) to carry out its payment in the budget.This article also examines the list and identifies the role of primary documents for the reflection amounts of the tax credit and tax obligations, and also schematically shows the sequence of the primary generalizations of VAT settlements.It is proved that the existence of problems account for the reflection and support of settlements with the budget on VAT, different methods of calculating VAT for the purposes of accounting and taxation and frequent changes in tax and accounting legislation, there is a need to identify ways of improving the reflection of the VAT in the accounting system.The study proposed the directions of improvement of VAT on enterprises in Ukraine, in particular the VAT using the «accrual» basis, simplifying the recording restrictions on sub-accounts 643 and 644, the introduction to the Order on accounting policies such a clause in part of any taxes as, for example, «Organization of accounting of tax payments» and the like.
Keywords: accounting, accounting policy, tax bill, tax liability, tax credit, value added tax